INTER-SECTIONS. THEORY-PRACTICE IN THE WRITING CENTER (Editors: Joan A. Mullin & Ray Wallace) - Rogers, Jacqueline McLeod (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1995)
Joan A. Mullin & Ray Wallace (Editors). INTER-SECTIONS. THEORY-PRACTICE IN THE WRITING CENTER. Urbana, IL: National Council of Teachers of English. 1994, 196 pp. $19.95. ISBN 0-8141-2331-T.